Nghiên cứu biến động bờ biển vùng Châu thổ Sông Cửu Long - Dỹ, Nguyễn Địch; Lâm, Doãn Đình; Sơn, Phạm Quang; Hà, Vũ Văn; Vĩnh, Vũ Văn; Quân, Nguyễn Công; Tuấn, Đặng Minh (Vietnam Journal of Earth Sciences, 2012)
SummaryResearching on variation of coastal areas in Cuu Long deltaResearching on variation of coastal area in Cuu Long delta was based on chain dataset from 1952 to 2006, including : high resolution satellite photographs, air photographs and topographic maps. The results show that study areas have been changed by natural and human factors.The Ba Lai and Bat Xac areas are 2 within 9 river mouths in researched area being changed the most. The stream of Ba Lai was disappeared by retaining dam in 1999 while Bat Xac was infilled since the beginning of 20th by the sand bar developed cross the stream.The Tien river mouths were being washed out and accretted alternately while the accretion are dominant in the Hau river mouths.